Development, implementation and early results of a 12‐week web‐based intervention targeting 51 children age 5-13 years and their families - Annelie Thorén; Annika Janson; Erling Englund; Sven‐Arne Silfverdal (Wiley, 2020)
Summary Background Internet‐based treatments have proven effective for various health issues. There is a need to scale up interventions targeting children with obesity, also in less densely populated areas where the prevalence in many countries is higher than in urban areas. The aim of this study was to design and implement an internet‐based program as an add‐on to standard treatment for childhood obesity. Methods Web‐Childhood Obesity Prevention (Web‐COP) was a prospective feasibility study with a pre‐ post‐ design. The intervention consisted of four group‐based education sessions at the clinic, physical activity on prescription, and a new 12‐week internet‐based program. Web‐COP was offered to children with obesity (International Obesity Task Force Body Mass Index (IOTF‐BMI) ≥ 30 kg/m2) and their parents in two counties in Northern Sweden from August 2018 to June 2019. The primary outcome was change in BMI standard deviation score (BMI‐SDS). Results The study included 55 children 5-13 years of age. The internet‐based component was well received, and retention rate was 51/55 (92.7%). Data was analysed for 51 children. Mean BMI‐SDS was 3.3 at start and decreased by 0.2, 0.3, and 0.4 at two, four, and six months from baseline. Using a continuous algorithm, 42/51 (81%), children lowered their BMI‐SDS and 33/51 (65%) lowered their BMI. Conclusion Adding group sessions and an internet‐based program to standard care was feasible and two thirds of included children with obesity reduced their BMI.